Advancements in Transfer Learning Strategies for PET and MRI Brain Image Fusion - Amit Ganatra, Sonia Panesar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Multimodal medical picture fusion is a trending research topic, in which research is happening. Multimodal medical image fusion is a procedure that integrates information from several medical imaging modalities to provide a more useful and complete visual content in the same picture to do subsequent operations like image segmentation etc. Medical image fusion may be particularly advantageous for biomedical research and medical image analysis and to minimize both the scan duration and motion artifacts in scan. The merging of neuroimaging data may lead to new insights into brain function and structure. In this article, multiple deep learning techniques including pre-trained VGG19 model, ALEXNET model and DENSENET model are applied utilizing transfer learning methodology to merge MRI (Magnetic Resonance Imaging) and PET (Positron Emission Tomography) neuroimaging. As the availability to medical data is restricted, transfer learning is employed for feature extraction and save training time. The features are blended using a pre-trained VGG19 model, ALEXNET model and DENSENET model. The experimental findings of all the three models include both quantitative and qualitative assessment metrics analysis for fused picture and achieves superior overall performance than unimodal and feature-level fusion approaches, and that it beats state-of-the-art methods.